Impact of HIV on Global Health: A Comprehensive Review of Epidemiology and Interventions - Km Priyanka Singh; Rifat Siraj (International Journal of Virus Studies, 2026)
H.I.V remains a significant health issue of great concern to the world and with great impact to the individuals and communities on a global scale. This is a comprehensive literature review on the epidemiology of HIV, including both the world prevalence of HIV and the regional variations, especially in sub-Saharan Africa. It discusses the most important modes of transmission including sexual, blood, and vertical transmission and investigates the effectiveness of prevention measures including behavioral interventions, pre-exposure prophylaxis (PrEP) and the current research on vaccines. The obstacles therein encountered in resource-limited settings and the development of drug resistance are also covered in the review. In addition, it brings out international initiatives to contain HIV such as the 90-90-90 goals and the contribution of technology towards improving HIV care. There are directions in treatment of HIV in the future such as long-acting formulations of ART and possible cures. This review highlights the role of further research and policy formulation, as well as global community, in the fight against HIV epidemic and enhancing health outcomes of the affected populations.
Keywords: 90-90-90 goals; Art; HIV; HIV vaccine; PrEP; drug resistance; epidemiology; global health; prevention measures